Assessment of the Effect of Fleet Management Software on Operational Performance: A of Case of Tanzania Electric Supply Company Limited - Mohamed, Farida (AGUSPATI Research Institute, 2025)
This study examines the impact of Fleet Management Systems (FMS) on operational performance, with emphasis on the Transport Management Information System (FMS) implemented at the Tanzania Electric Supply Company Limited (TANESCO). Guided by the Technology Acceptance Model (TAM) and the Resource-Based View (RBV), the research analyzed perceived usefulness, perceived ease of use, and personnel proficiency as determinants of operational performance. A quantitative approach was applied, using structured questionnaires distributed to 85 fleet personnel, with 78 valid responses analyzed through descriptive statistics and multiple regression in SPSS. Findings revealed that perceived usefulness and perceived ease of use had significant positive effects, with ease of use being the strongest predictor. Personnel proficiency, though positively rated, was not statistically significant when controlling for other variables. The study concludes that FMS effectiveness depends more on usability and institutional integration than individual skill levels. Recommendations emphasize system usability enhancements, enterprise integration, and performance-linked training.